2020
DOI: 10.3390/microorganisms8030335
|View full text |Cite
|
Sign up to set email alerts
|

Digestive Ability, Physiological Characteristics, and Rumen Bacterial Community of Holstein Finishing Steers in Response to Three Nutrient Density Diets as Fattening Phases Advanced

Abstract: The aim of this study is to track the dynamic alterations in nutrient intake and digestion, rumen fermentation and plasma metabolic characteristics, and rumen bacterial community of Holstein finishing steers in response to three nutrient density diets as fattening phases advanced. A total of eighteen Holstein steers were randomly allocated into three nutrient density groups and steers in each group were fed under a three-phase fattening strategy, with nutrient density increased in each group when fattening pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 40 publications
3
22
3
1
Order By: Relevance
“…Another interesting observation was the greater relative abundances of Fibrobacteres, Kiritimatiellaeota, and Cyanobacteria during the dry season when the fiber content of the diet is highest. These bacterial populations appear to be positively correlated with the NDF and ADF content of the diet [ 55 ]. Fibrobacteres phylum is composed of a single cellulolytic genus; Kiritimatiellaeota has been suggested to be involved in fiber degradation; and the rumen associated Cyanobacteria group are polysaccharolytic organisms [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting observation was the greater relative abundances of Fibrobacteres, Kiritimatiellaeota, and Cyanobacteria during the dry season when the fiber content of the diet is highest. These bacterial populations appear to be positively correlated with the NDF and ADF content of the diet [ 55 ]. Fibrobacteres phylum is composed of a single cellulolytic genus; Kiritimatiellaeota has been suggested to be involved in fiber degradation; and the rumen associated Cyanobacteria group are polysaccharolytic organisms [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, fat sources, and emulsifier phases did not influence the carcass parameters of broilers. Better performance could also be related to better beneficial microbes in the gastrointestinal tract of broilers because it has been reported that in livestock production better rumen microbe (Su, 2013;Niu et al, 2017;Qiu et al, 2019a;Qiu et al, 2020) and hindgut microbes (Qiu et al, 2019b) enhance the productivity of animals. Our findings of carcass parameters are similar with the results of previous researchers (Zhao et al, 2015;Upadhaya et al, 2016;Upadhaya et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Birds were free from hunger and thirst and manged according to standard protocol of animal behavior and welfare (Muhammad et al, 2016;Aziz ur Rahman et al, 2017;Aziz ur Rahman et al, 2019;Muhmmad et al, 2020). The source of Mycoplasma synoviae: The Ningxia University laboratory had already identified and preserved the Ningxia G-1 strain Media and culture conditions: Mycoplasma synoviae special medium Main instrument of the experiment and reagents: Instrument and reagents used in the current experiment were Ultra clean table, Supplement instrument manufacturer, Biochemical incubator, Micro tissue grinding machine, Ultramicro UV spectrophotometer (Li et al, 2014;Niu et al, 2017;He et al, 2018;Xia et al, 2018a;Xia et al, 2018b;Li et al, 2019;Qiu et al, 2019a;Qiu et al, 2019b;Qiu et al, 2020), Fluorescence real-time quantitative PCR instrument Rehman et al, 2019;Chen et al, 2020), Electrophoresis instrument, Sequencing instrument (Li et al, 2019;Qiu et al, 2019a;Qiu et al, 2020), Pacific Biosciences. Genomic DNA Extraction Kit; Accel-NGS ® •XL; Qubit TM Experimental method: Culture of strain and whole genome sequence According to Mycoplasma synoviae strain amplification culture conditions, liquid culture, authenticate, DNA gene extraction by Mycoplasma synoviae was used as a template.…”
Section: Methodsmentioning
confidence: 99%